In Patients With Parkinson’s Disease in an OFF-Medication State, Does Bilateral Electrostimulation of Tibialis Anterior Improve Anticipatory Postural Adjustments During Gait Initiation? - Delafontaine, Arnaud; Fourcade, Paul; Zemouri, Ahmed; Diakhaté, D. G.; Saiydoun, Gabriel; Yiou, Eric (Frontiers in Human Neuroscience, 2021)
A complete lack of bilateral activation of tibialis anterior (TA) during gait initiation (GI), along with bradykinetic anticipatory postural adjustments (APAs), often occurs in patients with Parkinson’s disease (PD) in their OFF-medication state. Functional electrical stimulation (FES) is a non-pharmacological method frequently used in neurorehabilitation to optimize the effect of L-DOPA on locomotor function in this population. The present study tested the potential of bilateral application of FES on TA to improve GI in PD patients. Fourteen PD patients (OFF-medication state, Hoehn and Yahr state 2-3) participated in this study. They performed series of ten GI trials on a force-plate under the following experimental conditions: 1) GI without FES (control group), 2) GI with 2Hz-FES (considered as a very low FES frequency condition without biomechanical effect; placebo group) and 3) GI with 40Hz-FES (test group). In 2) and 3), FES was applied bilaterally to the TA during APAs (300 mA intensity/300 μs pulse width). Main results showed that the peak of anticipatory backward center of pressure shift, the forward center of mass (COM) velocity and shift at foot off were significantly larger in the 40 Hz FES condition than in the control condition, while the duration of step execution was significantly shorter. In contrast, the capacity of participants to brake the fall of their COM remained unchanged across conditions. Globally taken, these results suggest that acute application of 40-Hz FES to the TA may improve the capacity of PD patients to generate APAs during GI, without altering their balance capacity.